3 Level Ventilation: the First Clinical Experience - P. Torok; M. Majek; J Salantay; P. Candik; E. Drbjakova; S. Saladiak; J. Goryova; J Popadyak; I. Lakatos (Общая реаниматология)
Considering the issues of artificial ventilation (AV) in non-homogenous pathological lung processes (acute lung injury (ALI), acute respiratory distress syndrome (ARDS), pneumonia, etc.), the authors applied the three-level lung ventilation to a group of 12 patients with non-homogenous lung injury. Three-level ventilation was defined as a type (modification) of AV whose basic ventilation level was produced by the modes CMV, PCV or PS (ASB) and add-on level, the so-called background ventilation was generated by two levels of PEEP. PEEP (constant) and PEEPh (PEEP high) with varying frequency and duration of transition between the individual levels of PEEP. Objective: to elucidate whether in cases of considerably non-homogenous gas distribution in acute pathological disorders, three-level ventilation (3LV) can correct gas distribution into the so-called slow bronchoalveolar compartments, by decreasing the volume load of the so-called fast compartments and to improve lung gas exchange, by following the principles of safe ventilation. Results. 3LV was applied to 12 patients with severe non-homogenous lung injury/disorder (atypic pneumonia and ARDS/ALI) and low-success PCV ventilation after recruitment manoeuvre (PaO2 (kPA) /FiO2 = 5—6). There were pronounced positive changes in pulmonary gas exchange within 1—4 hours after initiation of 3LV at a fPCV of 26±4 breaths/min-1 and PEEPh at a fPEEPH of 7±2 breaths/min-1 with a minute ventilation of 12±4 l/min. 3LV reduced a intrapulmonary shunt fraction 50±5 to 30±5%, increased CO2 elimination, with PaCO2 falling to the values below 6±0.3 kPa, and PaO2 to 7.5±1.2 kPa, with FiO2 being decreased to 0.8—0.4. Lung recruitment also improved gas exchange: with PEEP=1.2±0.4 kPa, static tho-racopulmonary compliance (Cst) elevated from 0.18±0.02 l/kPa to 0.3±0.02 l/kPa and then to 0.38±0.05 l/kPa. Airways resistance (Raw) decreased by more than 30%. Improved lung aeration was also estimated as a manifestation of gas distribution with a long time constant. After 5±1-day 3LV, the patients were switched to PS ventilation; after gradually reduction of ventilation maintenance, they were disconnected from a ventilator and transferred to a specialized unit. Conclusion. The small study group made it impossible to statistically assess outcomes; the clinical results are not at least contrary to the results of theoretical mathematic simulation of 3LV in mathematical and physical models. 3LV as compared with PCV applied within the first 2—4 hours of AV improved lung gas exchange. It can be a promising mode of ventilation for the lungs afflicted by a diffusive non-homogenous pathological process. Key words: artificial ventilation, three-level ventilation, acute lung injury, acute respiratory distress syndrome.